Word-Formation Analysis on Mark Zuckerberg's Post and Comment Section on Instagram - Mareta, Dinar Rosiana; Afriana, Afriana (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
Morphology is a field of science that investigates and studies basic forms in language, such as morphemes, the formation of affixes, words, and others. The purpose of this research is to find and identify the types of word formation in posts and comments on Mark Zuckerberg's Instagram account. This paper used theories from Yule (2020) to analyze the word-formation process. This study used the qualitative method to explain the data using sentences. In collecting data, this research used the observation method and note-taking techniques. The results of this study found 235 raw data points classified into types of word-formation processes. This research analyzed five types of word formation: acronym, derivation, compounding, coinage, and clipping. The types found along with the frequency of appearance are: acronym was found 24 times, derivation appeared 129 times, compounding 30 times, coinage 42 times, and clipping 10 times. The explanation provided above indicates that the most popular way for people to form new words and increase their vocabulary is by derivation, a sort of word construction that is extensively employed. Furthermore, the least common type is clipping in the data source of this study. The reason for this is that certain Instagram users who leave comments on Zuckerberg's posts rarely condense lengthy phrases into shorter ones.